(untitled) (South East Asia Journal of Public Health, 2016)
Universal health coverage (UHC) is currently at the center of discussion to strengthen health systems and improve health outcomes. The design and delivery of UHC requires an active engagement of various stakeholders viz. policy makers, program managers, civil society, private sector, academia and health professional associations. However, limited information is available on engagement of academia in discussions related to UHC. This study attempted to examine the perspectives of academia on advancing the agenda of UHC in India. A cross-sectional qualitative study was conducted with 62 stakeholders which included deans and senior faculty from 17 government and 15 private medical institutions across India, using a semi-structured questionnaire. Data analysis was done through free listing of responses, domain evolution and using qualifiers for semi-quantitative expressions. Clarity on concept of UHC and awareness on UHC developments was found low amongst stakeholders. It was strongly believed that not just tertiary care services but primary health care is more critical for UHC to succeed. Besides the responsibility of government, engaging other organizations was underlined. Approximately half of the respondents mentioned that their organization can support the provision of providing promotive, preventive, curative, and rehabilitative health services to achieve UHC. Stakeholders also felt that the tax-based and private health insurance can act complementary to each other, and should be promoted to improve health services coverage. Findings suggest that there is a strong need for engagement of academia for marching towards the goal of UHC. South East Asia Journal of Public Health Vol.5(2) 2015: 50-56